2020
DOI: 10.1002/nml.21412
|View full text |Cite
|
Sign up to set email alerts
|

The more you know, the more you give: Influence of online disclosure on European community foundations' donations

Abstract: Competition is high in the charitable contributions market, and donors demand to know how nonprofit organizations use the money they receive. In scrutinizing the variables that affect the capacity of nonprofits to attract donations, previous research has highlighted the positive influence of the amount of financial and performance information that nonprofits disclose through their websites. This study explored whether the depth of the organizations' online disclosures also affects these donations. In line with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
1
14
1
Order By: Relevance
“…Our results are consistent with those of those studies that argue that donors reward nonprofits that disclose large amounts of financial and performance information [17,63,64]. Furthermore, our results do not necessarily collide with those of [19], who do not detect any significant relationship between the financial information disclosed and the donations. These authors and, in general, all the works in previous literature, have analysed the donations as a whole, whilst our paper split those donations depending on the source from which they come.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those of those studies that argue that donors reward nonprofits that disclose large amounts of financial and performance information [17,63,64]. Furthermore, our results do not necessarily collide with those of [19], who do not detect any significant relationship between the financial information disclosed and the donations. These authors and, in general, all the works in previous literature, have analysed the donations as a whole, whilst our paper split those donations depending on the source from which they come.…”
Section: Discussionsupporting
confidence: 92%
“…To answer this question, this study examines the corporate reports of non-profits listed by the Spanish Development NGO Coordinator (CONGDE) in 2015. Other authors [18,19] have analysed the relationship between donations and the information disclosed by NGOs in different countries (Italy, UK and the USA). All of them have considered the set of donors as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Despite evidence of enhanced public confidence resulting from voluntary web disclosure practices, NPOs have failed to practice this even when regulatory agencies have been calling for the public disclosure of information (Blouin, Lee & Erickson, 2018). In an examination of websites belonging to community foundations in the UK and Italy, Rossi et al, (2020) found that information sharing was capricious, with few sharing information such as organisation priorities and longterm goals. Cordery et al (2019) opine that poor reporting practices are also the result of NPOs being guided by varying local requirements rather than a globally accepted set of standards.…”
Section: Reporting Outcomes and Impact Through Web Disclosure Practicesmentioning
confidence: 99%
“…Because disclosure can minimize information asymmetries, transparency has become a critical method for stakeholders, especially regulators and donors, to evaluate and monitor the performance of charitable organizations. The information senders can gain a slew of positive outcomes, such as organizational efficiency (Rocha Valencia, Queiruga, & González-Benito, 2015), trust (Schnackenberg & Tomlinson, 2016), and donations (Deng et al, 2015;Rossi, Leardini, & Landi, 2020;Saxton, Neely, & Guo, 2014). In practice, foundations mainly disclose their financial and nonfinancial information via annual reports, audited financial statements, and other recognized forms.…”
Section: Theoretical Explanations Of Information Disclosurementioning
confidence: 99%